Pendampingan Membangun Pemimpin Hamba Di Sekolah Tinggi Theologia Ebenhaezer - Sri Wahyuni Kusradi; Marlon Butarbutar; Ferdinan Pasaribu (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
This article intends to describe a pattern of mentoring to shape the students of Ebenhaezer Theological Seminary (Ind. STTE) as servant leaders. This is motivated by the lack of the number of servants of God who can become a leader at the same time. There is also the view that a true leader is only born, not formed. There are many discussions about Servant Leader, but this article intends to discuss how to be mentored informing as a servant leader in the STTE. In this article, the author uses qualitative methods. To find this problem, the writer interviewed several students who were being formed in the STTE. The writer also tried to find a theoretical basis for nurturing or mentoring to form Servant Leaders and make them relevant in the formation of Theology students. Based on this evaluation, it can be seen that effective tutoring or mentoring can help students become powerful Servant leaders.